Endothelial αvβ3 integrin induction during hypoxia protects blood–brain barrier integrity - Sebok K. Halder; Violaine D. Delorme-Walker; Richard Milner (Proceedings of the National Academy of Sciences, 2025)
The blood–brain barrier (BBB) is critical for maintaining cerebral homeostasis, and its deterioration with age is an important pathogenic factor in the etiology of vascular dementia. Extracellular matrix–integrin interactions play a central role in regulating vascular stability. The αvβ3 integrin is not expressed by brain endothelial cells under stable conditions but is strongly induced by hypoxia. However, it is currently unclear whether αvβ3 integrin exerts a destructive or protective influence on BBB integrity. In young (8 to 10 wk) and aged (20 mo) mice, we examined the impact of a function-blocking β3 integrin antibody as well as the inhibitory peptide cilengitide on BBB disruption during exposure to CMH (8% O 2 ). Hypoxic induction of brain endothelial β3 integrin was much stronger in aged mice. In both young and aged mice, β3 integrin inhibition greatly amplified hypoxia-induced BBB disruption, correlating with loss of tight junction proteins and induction of the leaky BBB marker mouse endothelial cell antigen (MECA)-32. Consistent with this, β3 integrin null mice showed increased levels of hypoxia-induced BBB disruption and MECA-32 expression. Cilengitide also reduced the integrity of a brain endothelial monolayer in vitro, prevented β3 integrin localization to focal adhesions, and reduced expression of vascular endothelial (VE)-cadherin and tight junction proteins. These observations suggest that hypoxic induction of endothelial αvβ3 integrin enhances BBB integrity by stabilizing endothelial adhesion. This raises the interesting possibility that pharmacological upregulation of endothelial αvβ3 integrin in the aged brain might hold therapeutic promise for vascular dementia.